(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2023)
The present article named ‘The biographical history of bediya tribal people : in context of Tarashankar Bandopadhyay’s short stories’ revolves around one of India’s primitive tribal communities called Bediya as depicted in the short stories by Tarashankar Bandopadhyay. Their history and their social life are observed and people document a historical account or a complete profile of the socio- economic as well as cultural life of the bediya people, which possesses vast literary, historical, archaeological, anthropological and social value.